[Evaluating interventions aimed at promoting information utilization in organizations and systems?] - KEDOTE, MARIUS; CONTANDRIOPOULOS, Damien; Brousselle, Astrid (My University, 2008)
This paper presents a theoretical and practical framework for evaluating interventions aimed at promoting information utilization in organizational decision-making. The framework integrates three distinct yet complementary theoretical perspectives on information utilization in politico-administrative systems: (1) the literature on evaluation utilization, (2) current thinking on knowledge transfer (KT) in the health policy field and (3) approaches derived from the analysis of lobbying in political science. Our analysis calls into question the relevance of effect analysis in evaluating organizational or policy-level KT initiatives, but also suggests dimensions that should be explored when evaluating KT initiatives. We conclude that there are probably trade-offs to be made between the effectiveness of KT and the scientific robustness and validity of the information transmitted.